Are worry, rumination, and post-event processing one and the same? Development of the repetitive thinking questionnaire - McEvoy, Peter; Mahoney, A.; Moulds, M. (Pergamon, 2010)
Accumulating evidence suggests that repetitive negative thinking (RNT) is a transdiagnostic phenomenon. However, various forms of RNT such as worry, rumination, and post-event processing havebeen assessed using separate measures and have almost exclusively been examined within the anxiety, depression, and social phobia literatures, respectively. A single transdiagnostic measure of RNT would facilitate the identification of transdiagnostic maintaining factors of RNT, and would be more efficient than administering separate measures for each disorder. Items from three existing measures of RNT were modified to remove diagnosis-specific content and administered to a sample of undergraduate students (N= 284). Exploratory factor analysis yielded two factors labeled Repetitive Negative Thinking and Absence of Repetitive Thinking (ART). The RNT scale demonstrated high internal reliability and was associated with anxiety, depression, anger, shame, and general distress. Moreover, the RNT scale was associated with constructs that are theoretically related to engagement in RNT, including positive and negative metacognitions, cognitive avoidance, thought suppression, and thought control strategies. The ART scale had little predictive utility. Theoretical and clinical implications are discussed.